Customised customer support using a soft computing approach - Shah, Satya Ramesh; Roy, Rajkumar; Tiwari, Ashutosh; Majeed, Basim (Cranfield University, 2005)
This paper describes the research and development of a methodology to identify the type of information required by the service advisor (CSA) within customer contact centre (CCC) environment. Data was collected through case studies carried out within five customer contact centres to derive the categories for customers and advisors based on demographic, experience, business value and behavioural attributes. We provide the methodology to develop a fuzzy expert system which assigns a new customer or advisor to the predefined categories. The authors have explained the steps which were followed for the development of the fuzzy expert system. A prototype system has been designed and developed to identify the type of customer and CSA based on the demographic, experience and behavioural attributes. The authors illustrate analysis with real data, based on the work with large scale customer contact centres. Validation of the information requirement model was carried out at the contact centres.